Tinjauan Teologis tentang Tanah Menurut Kehidupan Atoni Pah Meto - Ezra Tari (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
The land crisis has begun amid rampant deforestation. The condition of the soil began to be arid and did not produce maximum results. The land is seen as an area that must be controlled and utilized as much as possible for prosperity. The land is often a source of dispute between humans. However, humans ignore environmental sustainability. The purpose of writing is to describe Atoni Pah Meto's life attitude, preserving nature by respecting local wisdom. The purpose of this research is to explore the meaning of land according to the life of Atoin Pah Meto. The method used is qualitative. The research approach is a literature review. Atoin Pah Meto is very concerned about everyday life. The values built are a brotherhood, love for the environment, and care. Second, the farming method is how Atoni Pah Meto behaves. Third: personality emerges from challenging working conditions. Personality strives well to achieve a decent life.